THE ROLE OF MODERN TECHNOLOGIES IN INCREASING THE EFFECTIVENESS OF LEARNING FOREIGN LANGUAGES - Khusanova, Sevinch; Usmonova, Maftuna; Bannopova, Zulhumor (INTERNATIONAL CONFERENCES, 2022)
The use of contemporary technology in the educational process has come under more and more scrutiny in recent decades. It incorporates cutting-edge technology as well as novel teaching techniques and learning strategies. Our primary objective in utilizing modern technologies in foreign language learning is to demonstrate how technology can be effectively used to enhance the quality of foreign language instruction, the formation and development of students' communicative cultures, and the acquisition of the practical mastery of a foreign language.